A new method to identify key match-play behaviours of young soccer players: Development of the Hull Soccer Behavioural Scoring Tool - Robinson, James; Cumming, Sean; Salter, Jamie; Toner, John; Towlson, Chris (PLoS ONE, 2024)
The aim of this research was to assess the validity and reliability of a newly developed scoring tool, designed for monitoring youth soccer players during match-play performance to support coaches/scouts with the talent identification process. The method used to design the Hull Soccer Behavioural Scoring Tool comprised of a five-stage process of (i) conducting an initial literature review to establish content validity (ii) gaining content validity through a cross sectional online survey (iii) establishing face validity via expert coach feedback (iv) conducting inter-rater reliability tests and (v) intra-rater reliability tests. In stage two, twenty-two soccer academy practitioners completed an online survey, which revealed that player behaviours such as resilience, competitiveness, and decision making were all valued as the most important behavioural characteristics by practitioners (90.9%), whilst X-factor was valued as least important by a significant amount (27.2%). Stages three to five of the testing procedure included a sample of four academy coaches not involved in the preceding stage. Twenty male collegiate soccer players (under-16 to under-18) involved in the study took part in four versus four smallsided games (SSG) in a 'round-robin' tournament across three weeks which accumulated 14 SSG's, 100-140 minutes of playing time and 70-98 individual player grades. Two of the four academy coaches watched the SSG's and used the Hull Soccer Behavioural Scoring Tool to assess live evidence of desirable player behaviours, which was subsequently followed by retrospective video analysis for intra-rater reliability testing. The remaining two academy coaches watched the same SSG retrospective video footage to test for inter-rater reliability. Reliability results revealed an acceptable level of agreement with scores between 81.25%-89.9%for inter-rater whilst intra-rater provided scores between 80.35%-99.4%. Preliminary evidence here suggests that the Hull Soccer Behavioural Scoring Tool is both a valid and reliable method to assess desirable player behaviours during talent identification processes. Thus, youth soccer practitioners and researchers should seek to test and further validate the tool in order to confirm its utility as a means of measuring behavioural characteristics of youth soccer players.
Keywords: Multidisciplinary